Amnesic patients have residual prospective memory capacities. Issue 3 (3rd April 2019) - Meier, Beat; Fanger, Severin; Toller, Giannina; Matter, Sibylle; Müri, René; Gutbrod, Klemens
Abstract: Objective: To investigate, in two separate studies, whether amnesic patients with a severe memory impairment can learn to perform a habitual prospective memory task when they receive immediate feedback on prospective memory failures (Study 1) and whether amnesic patients are able to benefit from previous habitual prospective memory performance after a 24-h retention interval.Method: A prospective memory task was embedded in a lexical decision task (Study 1) and in a perceptual discrimination task (Study 2). Performance was compared across test halves. Participants received immediate performance feedback on prospective memory failures that served as a reminder for the prospective memory task. A retest was performed after 24 h in Study 2, but without immediate feedback in the first test half.Results: In Study 1, amnesic patients performed at a lower level than the control group, but they improved significantly across the experiment. In Study 2, the results of the first session replicated this pattern. The results of the second session showed a performance breakdown in amnesic patients. However, one single reminder was enough to boost performance again on the level of the second part of day one.Conclusions: This indicates that amnesic patients have residual prospective memory capacities and that providing immediate feedback is a promising strategy to draw on these capacities.